PENGGUNAAN PUPUK NPK MUTIARA UNTUK PENINGKATAN PERTUMBUHAN TANAMAN GAHARU Aquilaria spp PADA LAHAN TERBUKA DI TANAH ULTISOL - Fiolita, Vinny; Muin, abdurrani; Fahrizal, . (JURNAL HUTAN LESTARI, 2017)
Gaharu plants (Aquilaria spp.) can only be grown under shade in the first stage of the plant because this plant has a semi-tolerance silvens. This condition of gaharu make difficult to grow under the open, so it’s needed the applying of Mutiara NPK fertilizer. This study aims to determine the effect of NPK Mutiara fertilizer on the growth of gaharu in open field. The research was conducted at Trial Garden of Tanjungpura University in Pak Laheng Village, Toho Sub-District, Mempawah District until the plants are12 weeks old. Research Methods used Completely Randomized Design (RAL). Treatment of the research consisted of: without NPK Mutiara fertilizer;NPK Mutiara 50 gram/plant; and NPK Mutiara 100 gram/plant, with six replications/handling. The results showed that at the age of 12 weeks, Mutiara NPK fertilizer can accelerate the growth of height, diameter and number of leaves. The best dose of fertilizer to accelerate plant growth is 100 grams/plant.Keywords: Aquilaria spp, NPK Mutiara Fertilizer, and Ultisol